2020
DOI: 10.1002/celc.202000117
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Current‐Producing Human Oral Pathogens by Whole‐Cell Electrochemistry

Abstract: Extracellular electron transfer (EET) via cell-bound redox enzymes and/or redox shuttles is extensively studied in environmental bacteria. Meanwhile, EET capable pathogens have been identified in the human gut. However, other EET-capable bacterial niches where possible biofilm infections are prominent have scarcely been explored. Herein, we electrochemically characterized human oral biofilm pathogens, Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, to examine their EET capability. Both stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The multicellular filaments with hundreds of cells arranged end-to-end resulted in the enhanced EET ability to electrodes [ 36 ]. Similarly, given that filamentous C. matruchotii is discovered as an electroactive oral pathogen in this study and some other oral biofilm pathogens such as Streptococcus mutans [ 16 ], Aggregatibacter actinomycetemcomitans [ 6 ], Porphyromonas gingivalis [ 6 ] and Capnocytophaga ochracea [ 38 ] have already been shown to have EET capability are well connected with C. matruchotii , which nucleates the plaque-characteristic consortium according to the spatial organization in oral biogeography [ 17 ], it can be anticipated that long range electron transport is supported by C. matruchotii and the whole oral biofilm is electrically conductive. Based on the previous findings that in the oral polymicrobial biofilm, consortium consists of radially arranged taxa, organized around cells of filamentous Corynebacteria with anaerobic taxa in the interior and facultative or obligate aerobes tend at the periphery of the consortium [ 17 ], we can purpose that this arrangement may support electrically coupled organics oxidation and oxygen reduction in oral polymicrobial biofilm as in the cases of long-range EET in natural environments.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The multicellular filaments with hundreds of cells arranged end-to-end resulted in the enhanced EET ability to electrodes [ 36 ]. Similarly, given that filamentous C. matruchotii is discovered as an electroactive oral pathogen in this study and some other oral biofilm pathogens such as Streptococcus mutans [ 16 ], Aggregatibacter actinomycetemcomitans [ 6 ], Porphyromonas gingivalis [ 6 ] and Capnocytophaga ochracea [ 38 ] have already been shown to have EET capability are well connected with C. matruchotii , which nucleates the plaque-characteristic consortium according to the spatial organization in oral biogeography [ 17 ], it can be anticipated that long range electron transport is supported by C. matruchotii and the whole oral biofilm is electrically conductive. Based on the previous findings that in the oral polymicrobial biofilm, consortium consists of radially arranged taxa, organized around cells of filamentous Corynebacteria with anaerobic taxa in the interior and facultative or obligate aerobes tend at the periphery of the consortium [ 17 ], we can purpose that this arrangement may support electrically coupled organics oxidation and oxygen reduction in oral polymicrobial biofilm as in the cases of long-range EET in natural environments.…”
Section: Discussionmentioning
confidence: 95%
“…Single-potential amperometry (SA) and differential pulse voltammetry (DPV) measurements were conducted with an automatic polarization system (VMP3, Bio Logic Company, France) as reported earlier [ 22 , 42 ]. The following conditions were used for DPV measurements: pulse increments 5.0 mV, pulse amplitude 50 mV, pulse width 300 ms and a pulse period of 5.0 s. Supernatant exchange experiments and scanning electron microscopy (SEM) observations were performed as explained in our previous study [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroactive organisms can be found in all three domains of life, being ubiquitous in distinct environments, including lakes, soils as well as in deep-sea hydrothermal vents [11] , [12] . Recently, is has been demonstrated that these organisms are also present in the human digestive system [16] , [17] , in the mouse gut microbiome [18] , [19] , [20] and oral plaque [21] , with some of them associated with infectious diseases [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%